Investigating dual roles as being a part-time and university student: A narrative inquiry an EFL student - Anissa Octaviafitri Widodo (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
This narrative study is the experiences of an English student who are also working as a part-timer. The data study of collecting through in-depth interviews. The interview was done in two days. The expected results of this research are students who are studying and working as part-timers can manage or manage their daily time better and more effectively so that assignments are always fulfilled, and grades during lectures do not decrease due to fatigue after working as a part-timer. The implication is that by listening to the stories of these students, teachers or lecturers are advised to provide more intensive treatment to students who study while working so that it is fairer.